ANXIETY, STRESS AND COPING STRATEGIES IN UKRAINIAN MEDICAL STUDENTS AFTER THE YEAR OF THE RUSSIAN-UKRAINIAN WAR - Ogorenko, V.V.; Kyrychenko, A.H.; Kornatsky, V.M.; Shornikov, A.V.; Tymofeyev, R.M.; Poliakova, O.O.; Shirokov, O.V. (World of Medicine and Biology, 2023)
In order to study the influence of coping mechanisms on the level of anxiety and stress in students of higher medical education under martial law, 314 students of the Dnipro State Medical University were interviewed. The median level of anxiety was found to be 7 (4;11) points, with a noticeable difference between men and women. The median level of stress severity was 5 (4;7) points, with a significant difference between men and women. Adaptive cognitive strategies were the most prevalent (45.5 %) in the sample, while adaptive, relatively adaptive, and non-adaptive strategies were found in comparable frequency (27.1 % and 27.4 %, respectively). It has been determined that implementing adaptive emotional strategies decreases the likelihood of experiencing significant levels of anxiety while employing maladaptive emotional strategies increases the risk by 2.79 times. The utilization of other coping mechanisms does not appear to have a significant impact on the chances of developing severe anxiety.
Keywords: psychoemotional state; coping strategies; anxiety; stress; GAD-7 scale; coping behaviour